If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -3) + -3x = 5 Combine like terms: 5 + -3 = 2 2(2) + -3x = 5 Multiply 2 * 2 4 + -3x = 5 Solving 4 + -3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 5 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 5 + -4 -3x = 5 + -4 Combine like terms: 5 + -4 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333
| 5(-4)-6-7(-4)=2 | | -7+-10P*2+-9(-10P*2+1)= | | (3y+100)+(y+80)=180 | | -5-15+1=14y-32-y | | -5x-2-10=2-(-2+4) | | 75-2x=-15 | | 16+2f=22 | | 2b+4=b-3 | | 20b^2-136b-28= | | (3/4)x=(5/8) | | 4(5x-7)=56 | | X+1+1=6x-5x+2 | | .40x+.1=.60 | | N=-300+15N | | 5a+2+2a-7+4a=7 | | 6z+19=4z+19 | | -5x-2-10=2-(x+4) | | 85l=685 | | 3(X+1)=2X+24-X | | -3(y-7+3)+3=0 | | 6g+4(g)=1-g | | -x+x=91+7 | | X=-7y-10 | | -2x-6=-2x-4 | | 2.39=x-40 | | 10+9C+5C*2-4+6C= | | a-2-2+15=1+3a | | 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 |